Influence of preoperative variables on the 3-month functional outcomes of the Vivity extended depth-of-focus intraocular lens: a prospective case series - Giacomo Savini; Alice Galzignato; Catarina P. Coutinho; Jinhai Huang; Yue Wu; Piero Barboni; João Mendanha Dias; Filomena J. Ribeiro; Domenico Schiano-Lomoriello (Eye and Vision)
Abstract Background To investigate the functional results of the AcrySof IQ Vivity (Alcon, Fort Worth, TX) extended depth-of-focus intraocular lens (EDoF-IOL) and explore correlations between the preoperative biometric parameters and the postoperative functional outcomes. Methods In a prospective, single-center, non-randomized study, axial length, keratometry, anterior chamber depth, scotopic and photopic pupil diameters, pupil decentration, corneal asphericity, corneal higher-order aberrations (HOAs), coma and spherical aberration were measured preoperatively. The EDoF-IOL was implanted bilaterally. Three months postoperatively, manifest refraction, monocular and binocular uncorrected and corrected visual acuity at 4 m, 66 cm and 40 cm, binocular defocus curve, binocular contrast sensitivity, halometry and Strehl ratio were measured. Visual disturbances and spectacle independence were assessed with McAlinden and IOLSAT questionnaires, respectively. Assuming a minimum Pearson r correlation coefficient between variables of 0.5 with a power of 80% and a P value less than 0.05, a minimum sample size of 29 (58 eyes) cases was required. Results Forty-three patients were enrolled. Binocular distance corrected visual acuity was lower than 0.1 logMAR for a defocus between + 1.0 and − 1.5 D. The mean values at 66 cm and 40 cm were − 0.07 ± 0.06 and 0.19 ± 0.13 logMAR, respectively. McAlinden’s questionnaire revealed mean scores close to zero for all questions. The IOLSAT questionnaire showed that spectacles were never used for distance and intermediate vision. Regression analysis did not disclose any significant correlation between the preoperatively measured variables and the postoperative outcomes, with a few exceptions: preoperative higher order corneal aberrations were correlated to halometry area (r2 = 0.2592, P = 0.0006) and the Q value to contrast sensitivity (r2 = 0.1717, P = 0.00574) under photopic conditions with glare at a spatial frequency of 18 cpd and without glare for all spatial frequencies (P < 0.01); it was also correlated to contrast sensitivity under mesopic conditions without glare at a spatial frequency of 12 cpd (r2 = 0.2311, P = 0.0011). Conclusions In healthy unoperated eyes, the visual outcomes for this EDoF-IOL are independent of most of the patients’ preoperative parameters. Attention should be paid to preoperative corneal aberrations and asphericity, which did not lead to visual disturbances, but may be potential sources of halo and reduced contrast sensitivity.